Ideas work: a study of learning in network contexts: the case of the UK television industry - Tempest, Susan (2000)
A growing literature contends that organisational learning is a source of competitive advantage for firms seeking to adapt their strategies to rapidly changing environments. The 21st Century as the age of learning organisations and knowledge work is an inspiring vision. However, much of the existing organisational learning literature assumes that the locus for learning is within neatly bounded firms. Less appears to be known about the learning issues facing firms that are reliant on external relationships with mobile, contract labour, suppliers and customers. This thesis focuses on learning and knowledge development in the UK television production industry. An industry where ideas realisation occurs across firm divides, in flexible production networks of core employees and freelance knowledge workers. A conceptual tool, The Knowledge Chain, is developed, herein, to highlight the key learning processes arising in such fluid, network production contexts. It is contended, herein, that the network arrangements used to organise production in the UK television industry raise challenges for firms seeking the control of knowledge resources. Indeed, attempts to codify the wide array of knowledge, on which network production builds, may be a futile exercise that squanders scarce resources. However, this thesis suggests that firms operating across such networks can still profit from the learning of a wide array of external production partners by building strategic learning relationships and effective learning contexts that facilitate knowledge sharing, application and development drawing on many more brains than a firm could afford to employ. Facilitating learning relationships with external partners can bring strategic benefits including leveraged learning to outpace competitors, and insurance against strategic myopia and the intra-firm insularity of group-think. Nevertheless, when key workers are not internal employees and production defies firm boundaries, profiting from learning becomes a more complex relational and contextual challenge than much of the existing literature implies.